Analysis Of Riba in Household Consumer Debt Among The Community Of Sindanghaji Village - lestari, Ayu Gumilang; Rendy Muhammad Susilo, Aa; Reza Abdul Aziz, Faisal; Rahayu , Sinta; Magfirah , Siti; Rusmiyati, Kurnia (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2024)
This study explores the impact of consumptive debt practices involving usury (riba) in the community of Sindanghaji Village, Majalengka Regency, Indonesia. Amidst rapid economic growth and increasing inequality, rural communities face difficulties in meeting their basic needs, leading them to resort to borrowing from financial institutions such as "Bank Keliling" or "KOSIPA." These loans often come with high interest rates, which contravene Sharia principles prohibiting usury. Employing a qualitative method with a case study approach, this research analyzes community perceptions of usury and consumptive debt. The findings indicate that while these loans assist in meeting consumptive needs, they also risk exacerbating debt burdens and triggering social issues such as fraud and violence. The study underscores the necessity for financial alternatives aligned with Sharia principles and improved financial planning strategies to enhance community welfare.